How zoo-housed chimpanzees (Pan troglodytes) target gestural communication within and between age groups - Oliveira, Miguel Filipe da Silva (2020)
Gestural communication among nonhuman primates evolved as a response to their complex social environment. In this scope, males and females, adults and nonadults employ different gestures, probably due to their distinct social roles. In this study, a within and between age group analysis of the gestures produced in different contexts was carried out. For this purpose, a community of 16 captive chimpanzees (Pan troglodytes) was observed during a 3-month period. Initially, data were collected through ad libitum sampling in order to identify their gestural repertoire. Subsequently, focal sampling was used to identify who gesticulated with whom and in what context. Overall, the results showed that juvenile chimpanzees tend to direct their gestures to different age groups according to the context; more specifically, juvenile chimpanzees frequently gesticulate within their age group in play contexts, and with older individuals in locomotion and affiliation contexts. Based on this, a certain degree of flexibility in juvenile chimpanzees gestural signalling is suggested, to the extent that they rather direct their gestural signs to chimpanzees of the same age group with the aim of involving themselves in the activities’ context in which the gestural sign is produced.